The great sheep shenanigans - Bently, Peter, 1960- (Andersen Press USA : Distributed in the United States by Lerner Pub. Group, 2012)
A confident wolf named Lou Pine is in for a surprise when he disguises himself and tries to outwit the "dumb" sheep.